The application of the dimensions of TQM and its impact in enhancing the satisfaction of the taxpayers: Applied Study in the General Commission for Taxes (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The concept of TQM is based on one of the concepts that combine administrative and innovative methods. The aim of the research is to demonstrate the dimensions of TQM in enhancing the satisfaction of the taxpayers through a survey of a sample of officials in the General Authority for Taxation and 50 officials. In the collection of data and information, and the results were analyzed using the SPSS program to find the most important compounds and factors in he method of analysis.The research problem was represented by the non-application of the General Authority for Taxation to the entrances and modern practices in the administrative work. The results of some of the complications that accompany the tax accounting process, which affect the nature of the relationship between the taxpayer and tax administration as well as the taxpayer's feeling of dissatisfaction, With a significant effect of factors and variables of total quality management in the satisfaction of taxpayers, and the researcher reached a set of conclusions was the most important: To meet the needs and desires of the taxpayers to implement the TQM and is available to the General Authority for Taxation Cannery The need for full Application of Total Quality Management.